Photochemical oxidation and landfarming as remediation techniques for oil-contaminated soil - M. Mambwe; K.K. Kalebaila; T. Johnson (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: With technological advances, mining industries use more crude oil and its products. Finding fast, effective, and eco-friendly repair techniques for oil-contaminated soil is crucial. Clay–titanium dioxide/manganese was used to investigate how oil breaks down in soil under sunlight. Various soil remediation techniques have been used to discard oil pollutants in soil. A polluted site must be cleaned effectively with a suitable method. Natural attenuation takes too long to produce positive results, whereas landfarming can produce toxic intermediates due to the organisms’ inability to degrade other oil components. Photochemical oxidation is a promising eco-friendly technique that can be employed as an alternative remediation method. The speed at which natural attenuation, photochemical oxidation, and landfarming could remove oil from contaminated soils was examined. Photochemical oxidation’s superiority as a remediation technique over landfarming is hypothesized.METHODS: Using clay modified with titanium dioxide and manganese, the effectiveness of landfarming and photochemical oxidation on oil-contaminated soil was investigated, together with the processes’ kinetics. To establish the processes’ effectiveness and kinetics, the oil residue was calculated at 7-day intervals for 35 days.FINDINGS: Initial oil concentration was 56.6 milligrams per kilogram, and degradation rates ranged from 23.91-80.47 percent. Highest oil reduction was 10.86 milligrams per kilogram. Combined remediation (biocarb and grafted clays) produced high degradation rate constants, k (0.046-0.049/day) and low degradation half-lives, t½ (15.2, 17.4 days). Photochemical oxidation rate constants ranged from 0.015-0.03984/day and half-lives ranged from 17.395-44.971 days, whereas landfarming had a rate constant of 0.008 and half-life of 83.094. Natural attenuation had the lowest k (0.007) and longest half-life (t½) of 94.8 days. Significant differences in means were observed among treatments (control, biocarb, and bicarb + grafted clays) at p ≤ 0.05, suggesting that treatment caused oil decrease in microcosms for biocarb + grafted clays. Grafted clays plus biocarb show potential for combined remediation of oil-contaminated soil.CONCLUSION: One primary indicator used to assess treatments’ efficacy is oil reduction, calculated using difference in oil content in soil before and after remediation. This shows that oil can be quickly removed from oil-contaminated soil by using biocarb + grafted South Luangwa with 80 percent oil reduction. Results suggest that photochemical oxidation may be used to effectively degrade oil and shorten remediation time. Photochemical oxidation is environmentally friendly and degrades oil faster than landfarming. Zambia’s Mopani Copper Mines can consider adopting photochemical oxidation as a remediation technique in treating oil-contaminated soil.